Endurance training in the spontaneously hypertensive rat conversion of pathological into physiological cardiac hypertrophy - Garciarena, Carolina Denis (2009)
The effect of endurance training (swimming 90 min/d for 5 days a week for 60 days) on cardiac hypertrophy was investigated in the spontaneously hypertensive rat (SHR). Sedentary SHRs (SHR-Cs) and normotensive Wistar rats were used as controls. Exercise training enhanced myocardial hypertrophy assessed by left ventricular weight/tibial length (228±7 versus 251 ±5 mg/cm in SHR-Cs and exercised SHRs [SHR-Es], respectively). Myocyte cross-sectional area increased ≈40%, collagen volume fraction decreased ≈50%, and capillary density increased ≈45% in SHR-Es compared with SHR-Cs. The mRNA abundance of atrial natriuretic factor and myosin light chain 2 was decreased by the swimming routine (100± 19% versus 41 ± 10% and 100±8% versus 61 ±9% for atrial natriuretic factor and myosin light chain 2 in SHR-Cs and SHR-Es, respectively). The expression of sarcoplasmic reticulum Ca2+ pump was significantly augmented, whereas that of Na+/Ca2+ exchanger was unchanged (93±7% versus 167±8% and 158±13% versus 157±7%, sarcoplasmic reticulum Ca2+ pump and Na+/Ca2+ exchanger in SHR-Cs and SHR-Es, respectively; P<0.05). Endurance training inhibited apoptosis, as reflected by a decrease in caspase 3 activation and poly(ADP-ribose) polymerase-1 cleavage, and normalized calcineurin activity without inducing significant changes in the phosphatidylinositol 3-kinase/Akt pathway. The swimming routine improved midventricular shortening determined by echocardiography (32.4±0.9% versus 36.9±1.1% in SHR-Cs and SHR-Es, respectively; P<0.05) and decreased the left ventricular free wall thickness/left ventricular cavity radius toward an eccentric model of cardiac hypertrophy (0.59±0.02 versus 0.53±0.01 in SHR-Cs and SHR-Es, respectively; P<0.05). In conclusion, we present data demonstrating the effectiveness of endurance training to convert pathological into physiological hypertrophy improving cardiac performance. The reduction of myocardial fibrosis and calcineurin activity plus the increase in capillary density represent factors to be considered in determining this beneficial effect.